Attitude and Willingness for helping patients with Suicidal Behavior: A Comparative Study of Clinicians working in Psychiatry and Emergency Medicine Units - Syeda Ayat-e-zainab Ali; Tamkeen Saleem (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To compare the attitude and willingness of clinicians working in emergency medicine and psychiatry units to help patients who are exhibiting suicidal behavior. The study also aimed to investigate differences across male and female clinicians in their attitude and willingness to help patients with suicidal behaviour. Method: A comparative cross-sectional study was carried out between March 15, 2022, and January 10, 2023. A sample comprised of clinicians working in psychiatry and emergency medicine units (N = 130, 65=eThe data was gathered from Benazir Bhutto Hospital, Pakistan Institute of Medical Sciences, Fauji Foundation Hospital, CMH, Watim Medical Hospital, CDA Hospital, Pakistan Ordinance Factories Hospital, and Shifa International Hospital. Data was collected using the demographic sheet, and to measure the attitude and willingness for helping patients with suicidal behaviour, the Understanding Suicidal Patients Scale was used. Data was analysed using SPSS (V-25). Results: Participants’ ages ranged from 25 and older (M = 1.86, SD =.89). Most of them were males (51.5%), belonging to middle socio-economic status (n = 82, 63.1%), were married (50%), had a nuclear family background (67.7%), were working at Benazir Bhutto Hospital (36.9%), and were working for more than 8 hours (65.4%). Clinicians working at psychiatry units showed more positive attitude and willingness for helping patients with suicidal behaviour than emergency medicine units (p<.001). The results further indicated that female clinicians showed more positive attitude and willingness for helping patients with suicidal behaviour than male clinicians (p<.04). Conclusion: There is a need for crisis handling training of health care professionals not only for physical crises/emergencies but also for mental health crises in order to deliver better care and treatment to the patients in need of help. Also, there should be some mental health crisis management program in Pakistan that can educate/bring awareness on suicidal behaviours among the clinician, parents, and vulnerable individuals. Key Words: Suicidal Behavior, Clinicians, Attitude, Willingness